ON THE EFFECTIVENESS OF THE USE OF INNOVATIVE METHODS IN FOREIGN LANGUAGE CLASSES AT THE UNIVERSITY - Maxkamova , Shaxlo Xasanovna (Innovative Development in Educational Activities, 2023)
The article is devoted to solving the problems of methodological organization of the process of teaching English in higher education. In the article, by considering and studying the theoretical and methodological aspects of innovative teaching technologies, the most effective of them are substantiated in the context of solving the problem of choosing technologies and methods of teaching English in a modern university.